2023
DOI: 10.21203/rs.3.rs-2494599/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inhalable CAR-T Cell-Derived Exosomes as Paclitaxel Carriers for Treating Lung Cancer

Abstract: Background Non-small cell lung cancer (NSCLC) is a worldwide health threat with high annual morbidity and mortality. Chemotherapeutic drugs such as paclitaxel (PTX) have been widely applied clinically. However, systemic toxicity due to the non-specific circulation of PTX often leads to multi-organ damage, including to the liver and kidney. Thus, it is necessary to develop a novel strategy to enhance the targeted antitumor effects of PTX. Methods Here, we engineered exosomes derived from T cells expressing th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Paclitaxel was encapsulated in these CAR-Exos (PTX@CAR-Exos) and administered to lung cancer mouse models through inhalation. The results showed that inhaled PTX@CAR-Exos accumulated within the tumor area and signi cantly reduced tumor size, extended survival time, and exhibited lower toxicity [25][26][27][28]. Rezakhani et al's study used various EVs loaded with doxorubicin and paclitaxel to treat different types of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Paclitaxel was encapsulated in these CAR-Exos (PTX@CAR-Exos) and administered to lung cancer mouse models through inhalation. The results showed that inhaled PTX@CAR-Exos accumulated within the tumor area and signi cantly reduced tumor size, extended survival time, and exhibited lower toxicity [25][26][27][28]. Rezakhani et al's study used various EVs loaded with doxorubicin and paclitaxel to treat different types of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the unique properties of the exosomes, such as size (30-150 nm), density (1.1-1.18 g/ml), and evolutionary conserved set of protein molecules (CD9, CD63, CD81, Alix, and Tsg101), CAR-T cell derived exosomes can be isolated from culture medium using a variety of techniques, including ultrafiltration, ultracentrifugation, and affinity capture on antibody-coupled magnetic beads [114]. T cell exhaustion avoidance/boost the PTXinduced immunogenic cell death [121,122] Abbreviation: CAR: Chimeric antigen receptor, HEGFR: Human epidermal growth factor receptor, HER2: Human epidermal growth factor receptor 2, MSLN: Mesothelin, PD-L1: Programmed death-ligand 1, PTX: paclitaxel Before using CAR-T cell-derived exosomes in any clinical setting, it is definitely warranted to conduct preclinical studies to characterize them.…”
Section: Discussionmentioning
confidence: 99%
“…BC (TNBC) Granzyme B, PerforinInhibit tumor growth[71,118,120] [71, 118, 120] Mesothelin-positive Lung cancer Granzyme B, Perforin(PTX-based chemotherapy, Lip-CExo@PTX) Inhibit tumor growth/Enhance the antitumor effects[121,122] PD-L1 blocked PD-L1 on the tumors to Granzyme B, Perforin(PTX-based chemotherapy, Lip-CExo@PTX)…”
mentioning
confidence: 99%
“…Studies have shown that normal cells or tumor cells release exosomes through exocytosis, which are multivesicular body (MVB) formed by inward budding of vesicles in the late endosome, and PD-L1 on the cell surface enters MVB during endocytosis (122). Huang et al found that the expression level of circulating EVs in septic patients was higher than that in healthy controls, and it inhibited T cell function in a concentration-dependent manner, which was represented by significantly reduced expression of CD69, upregulated expression of PD-1 and increased proportion of Treg, w h i c h m a y b e o n e o f t h e m e c h a n i s m s l e a d i n g t o immunosuppression of sepsis (119). Kawamoto et al reported the presence of PD-L1 and PD-L2 on circulating exosomes in the plasma of septic patients and found elevated levels of b2 integrin and PD-L2 on exosomes in these patients (123).…”
Section: Exosomesmentioning
confidence: 95%
“…Studies have revealed that exosomes (EVs) play a crucial role in tumor-associated immune paralysis by acting as carriers for PD-L1 on PD-1 and inducing potent inhibitory signals (117)(118)(119). Recently, the involvement of EVs in the pathogenesis of sepsis has also attracted attention (120).…”
Section: Exosomesmentioning
confidence: 99%